2020
DOI: 10.1038/s41598-020-76590-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal impact of grazing, viral mortality, resource availability and light on the group-specific growth rates of coastal Mediterranean bacterioplankton

Abstract: Estimation of prokaryotic growth rates is critical to understand the ecological role and contribution of different microbes to marine biogeochemical cycles. However, there is a general lack of knowledge on what factors control the growth rates of different prokaryotic groups and how these vary between sites and along seasons at a given site. We carried out several manipulation experiments during the four astronomical seasons in the coastal NW Mediterranean in order to evaluate the impact of grazing, viral mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 76 publications
6
26
0
Order By: Relevance
“…Estimations of growth rates of a few broader taxonomic groups were previously reported that were usually based on microscopic FISH counts. Typically, target groups included Gammaproteobacteria and its subgroups Alteromonadaceae , NOR5/OM60, SAR86, the Roseobacter clade, and SAR11 of the Alphaproteobacteria and Bacteroidota ( 11 , 13 19 ). Even though these studies provided valuable insights into community growth dynamics, the phylogenetic groups they targeted were limited in number and lacked finer taxonomic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Estimations of growth rates of a few broader taxonomic groups were previously reported that were usually based on microscopic FISH counts. Typically, target groups included Gammaproteobacteria and its subgroups Alteromonadaceae , NOR5/OM60, SAR86, the Roseobacter clade, and SAR11 of the Alphaproteobacteria and Bacteroidota ( 11 , 13 19 ). Even though these studies provided valuable insights into community growth dynamics, the phylogenetic groups they targeted were limited in number and lacked finer taxonomic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…S2) and the standard deviation set to half the mean, or 0.25, the geometric distribution parameter p of the rRNA copy numbers was set to 0.8 (in the geometric distribution, (1 – p ) k –1 p, k is the copy number and p represents the fraction of the starting community with copy number = 1), the mortality rate δ was set to 0.07, the activation energy E was set to 0.33 eV, and the prefactor a set to 170,000. In case 2), the mean of the normal distribution of α ij was randomly drawn from a uniform distribution [0.1, 1] and the standard deviation was set to half the mean, the geometric distribution parameter p of the rRNA copy numbers was drawn from a uniform distribution [0.6, 0.9], the mortality rate δ was drawn from a uniform distribution [0.03, 0.2]( 42 ), and the activation energy E was drawn from a uniform distribution [0.1 eV, 0.6 eV] ( 71, 72 ), with the prefactor a set to the mean of 0.46e E /( k B *300) and 0.05 e E /(k B *,278) (ensuring that growth rates with the highest copy number at high temperature did not exceed realistic rates, and that the growth rate of species with copy number = 1 exceeded most mortality rates at the lowest temperatures).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the seasonal impact of grazing and viral mortality in the Mediterranean Sea, where higher grazing pressure and lysogeny were observed in the stratified nutrient-limited waters in summer (Sánchez et al, 2020), it will be important to further study the seasonal impact of dust deposition on trophic interactions and indirect cascading impact on microbial dynamics and community composition.…”
Section: Trophic Interactions After Dust Addition Under Present and Future Conditionsmentioning
confidence: 99%